Blastocystis hominis: occurrence in children and staff members of municipal day-care centers from Botucatu, São Paulo State, Brazil - Guimarães, Semíramis [UNESP]; Sogayar, Maria Inês Leme [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 1993)
To study the frequency of Blastocystis hominis among healthy individuals, feces were collected from 153 children and 20 staff members of some municipal day-care centers. Three separate stool specimens of each individual were processed by Lutz and Faust methods. From 173 studied individuals, 60 (34.7%) showed B. hominis, frequently in association with other intestinal parasites and/or commensals. B. hominis was found mainly in adults and children between 36 and 72 months old. All positive cases were detected only by Lutz method and the use of three stool specimens increased the positivity of the parasitological diagnostic.
Keywords: Blastocystits hominis; day care centers; children; staff members; stool